Estudo fenotípico e genotípico da produção de biofilme por Staphylococcus aureus isolados de leite bubalino e ambiente de ordenha - Almeida, Camila Chioda de [UNESP] (2014)
Staphylococcus aureus is the most common cause of mastitis in dairy herds due to its production of several virulence factors, including those related to its ability to colonize the teat parenchyma. The microbiological status of raw milk supplied to manufacturers may reflect on the final product and the associated risks to consumer health. Accordingly, the aim of this study was to isolate and characterize S. aureus strains from samples of Murrah buffalo milk, milking machines, water hoses from milking room and from the hands of milkers on a dairy farm located in Analândia – SP during the months of April, July, October, and November. Biofilm-producing capacity was evaluated in vitro” using a microtiter method and cultivation on Congo Red Agar (CRA). Antibiotic sensitivity testing was performed by the disk diffusion method and the identification of the genes involved in biofilm formation by Polymerase Chain Reaction (PCR). One hundred and forty-seven Staphylococcus spp. were isolated and 32 were identified as S. aureus. Of those isolates, 28.1% were positive for the icaA gene, 21.8% for the icaD gene, 28.1% for the clfA, 50.0% for the clfB, 53.1% for sarA and 50.0% for hla. All isolates produced slime on Congo Red Agar (CRA) and formed biofilms in a microtiter assay. Although the frequency of S. aureus was low, the stains isolated can be considered as potential zoonotic agents